(3Gdedc aGQhb GdChds (3bQU VhFj edjRQ(B]s ((3GdbGgQIs (3gGj ajdes, 1995)
(3Gdajde jJfGhd deMg JGQjNjI Yf CSQI eMeO Ydj hYgO Gdedc aDGO hJhdj Gdedc aGQhb GdChd YQT eUQ hbUI RhGLg HGdedcI aQjOI hGdeUGgQI Hjf eUQ hEjQGf HRhGL dCejQI ahRjI HTGg EjQGf TGgHhQ eMeO QVG Hgdhj hbjGe GdMQH GdYGdejI GdKGfjI hRhGL GdCejQI aJMjI ef QjGV ZGdj HGdNGQLjI hRhGL Gdedc aGQhb GdKGfj HGdedcI fGQjeGf UGOb Ke bjGe KhQI jhdjh SfI (B1952 (3hNdYg Yf Mce eUQ hJCejf bfGI GdShjS hMQH (B1956 (3hjfJgj Gdajde HhaGI Gdedc aGQhb aj efaGgs
(3gPG dajde QDjI TNUjI dMjGI Gdedc aGQhb GdChd edc eUQ GdSGHb hQHeG Jchf gPg GdQDjI bGHdI ddJcPjH Ch GdJUOjbs
(3GdESWhGfI JYed Ydj CLgRI (Bdvd (3hGdceHjhJQs
12 13
Keywords: (3GdCadGe GdhKGFbjIs -- (3ehGO SeYjI hHUQjIs; (3eGdJj ejOjGs -- (3cHGQs -- (3ehGO SeYjI hHUQjIs